ChemInform Abstract: One‐Pot Synthesis of Spiropyrroloquinoline‐Isoindolinone and Their Aza‐Analogues via the Ugi‐4CR/Metal‐Free Intramolecular Bis‐annulation Process. Issue 49 (December 2015) - Ghandi, Mehdi; Zarezadeh, Nahid; Abbasi, Alireza
Abstract: Combination of an Ugi four‐component reaction with two intramolecular cyclizations affords the title compounds.